KOMUNIKASI LINGKUNGAN SEBAGAI UPAYA PENCEGAHAN KERUSAKAN LINGKUNGAN KAWASAN WISATA (Studi Deskriptif Pada Pemerintah Kabupaten Pesisir Selatan di Kawasan Wisata Mandeh) - Aulira M Tan; Sarmiati Sarmiati; Elfitra Elfitra (Jurnal Komunikasi, 2019)
Enviromental problem that occur currently are increasingly damaging to the nature in tourist area of Mandeh by forest burning, mangroves hoarding, and the contamination that happens to the sea. Therefore, it needs a serious effort to build and increasing the concern of people around towards the environment to minimalizing the decrease in enviromental quality. This research using qualitative method by descriptive approaches to get the communication goals from Pesisir Selatan Enviromental Services towards the enviromental damage in tourist area of Mandeh. The relevancy of enviromental communication as an effort to communicate the enviromental sustainability, the researcher using communication planning theory that can help to build the awareness and concern for the society or industry in the enviromental surroundings. The result of this research shows that DLH (Pesisir Selatan enviromental services) using communication planning during their activity according to the 8 steps of enviromental communication, but it has not been done massively. Besides through a direct activity with the society such as socialization, training, coaching, forum group discussion and enviromental community, DLH also using media to share the information to the society such as using radio, SPM TV, the billboard, sign of prohibition and online media. Another finding obtained through communication planning analyze from DLH is they know the behaviour of society, knowing the potential of enviromental impact, and providing the options and direction, it turns out among them there is the existence of word of mouth in society.